The process of change to sustainable farming practices - Park, J.; Keatinge, J.D.H. (2000)
The sustainability of agricultural systems is under scrutiny in many parts of the world. In the European Union farming systems are increasingly subject to legislation aimed at controlling production or the environment. Against this background a wide range of research is being undertaken into new or alternative land use systems. In this paper it is argued that sustainability in effect provides parameters for this process of change. Therefore, one of the roles of researchers is to high light the options for change available to farmers and to suggest to policy makers the likelihood and ways of improving the uptake of desirable farming practices. Examples are drawn from a variety of research being undertaken in Agricultural Systems at the University of Reading. It is concluded that a systems approach must be an integral part of progress towards increasingly sustainable farming practices and to achieve this agricultural universities must maintain a strong systems research and teaching commitment.